‘We need more conversations like this’: The impacts of working with student pedagogic consultants in developing simulation-based pedagogies (Journal of Applied Learning and Teaching, 2024)
The growing global teacher recruitment and retention crisis has ensured that discussions regarding how best to promote preparedness for classroom practice are more important than ever, with significant implications for initial teacher education (ITE). Adopting a multi-stage collaborative autoethnographic inquiry approach, this research paper contributes to the emerging field of simulation-based pedagogies (SBP) in ITE, as well as the strong research base in other disciplines, by outlining the impacts of working with student pedagogic consultants (SPCs) upon staff professional understanding of the effective planning and implementation of SBP. Findings suggest that working closely with SPCs affirmed staff pedagogic choices in deploying SBP, indicating a shared understanding of the benefits of simulation, and provided valuable insider perspectives to enhance staff pedagogic understanding and suggest improvements to the design of simulation sessions. However, accounts also highlight challenges experienced in the pedagogic consultancy process itself, including logistical concerns such as the use of time; discussions around power dynamics; and tensions arising from epistemological differences between staff and students. The authors conclude by advocating both the wider adoption of SBP in ITE and further exploration of working in partnership with students as SPCs to inform, and improve, the design and implementation of such pedagogies.